Strategies for Sustainable Tourism Development in the Context of Old Parts of Isfahan, Presenting Priorities Using the Delphi Method - Amirhosein Halabian; Laleh Pooreydivand; Mehdi Abdollahzadeh; Zaynab Omrani Sardo (جغرافیا و پایداری محیط)
Tourism is a multifaceted activity and one of the most complex businesses with regard to human geography. The sustainable development in tourism planning is important since the development of tourism attractions and activities highly relies on the natural environment, historic heritage and cultural patterns. Historical and cultural fabric of the cities is part of the national capital not only due to their beauties, the persistence of collective memory ,and their function in establishing an identity for us, but also since they are residance of millions of people. However, these regions have negative features such the disturbance of perspective, lack of access to adequate facilities and equipment, economic and social distress and burnout in the body which , in turn, has led to the evacuation of large populations from these tissues. This research concerns with appropriate strategies for sustainable tourism development strategies with special focus on the older parts of this city. To achieve this goal Delphi Forum Polling Model has been used. This research has resulted in the classification of strategies for sustainable development of tourism in this region in order of priority.